Дослідження моделей та методів проективних методик тестування на основі природної мови - Світенко, Г. М. (ХНУРЕ, 2024)
This work is devoted to gather and analyze information for conducting research using projective testing methods based on natural language. It encompasses analyzing the subject area, identifying topic issues, selecting research methods, and planning the experimental part of the project. The work also involves assessing the applicability of thematic apperceptive testing (TAT) and the Dana assessment method as primary instruments. Large language models (LLM), including the LlaMa 2, RoBERTa, GPT models, will be utilized to analyze responses to the thematic apperceptive test in experimental part of further research.
Keywords: тестування на основі природної мови; природна мова